Clinicopathological and Prognostic Significance of Long Non-coding RNA MIAT in Human Cancers: A Review and Meta-Analysis - Wang, Yongfeng; Fu, Liangyin; Lu, Tingting; Zhang, Guangming; Zhang, Jiawei; Zhao, Yuanbin; Jin, Haojie; Yang, Kehu; Cai, Hui (Frontiers in Genetics, 2021)
Background: Although the treatment of cancer has made evident progress, its morbidity and mortality are still high. The early diagnosis of cancer can improve the prognosis of patients conspicuously. Therefore, it is urgent to find new tumor markers. LncRNA MIAT is a new tumor marker be found recently, but its functions in tumors and its relationship with clinicopathologic features and prognosis in patients are not exact. As a result, we carry out this meta-analysis to explore its effect on tumors. Methods: We searched PubMed, Embase, Web of Science, The Cochrane Library from inception to September 2020 to find correlational studies. Then, we extracted valid data and utilize Stata software to make forest plots. We used the hazard ratio (HR) or odds ratio (OR) with 95% confidence interval (CI) to evaluate the relationship between aberrant expression of MIAT and patients’ prognosis, clinicopathology. Results: The study included 21 studies finally, containing 2048 patients. Meta-analysis showed that overexpression of lncRNA MIAT was associated with poor prognosis (HR = 2.76, 95%CI, 1.69–4.49, P<0.001). Additionally, high expression of MIAT could forecast tumor size (OR = 2.26, 95%CI 1.34–3.81, P=0.002), distant metastasis (OR = 2.54, 95%CI 1.84–3.50, P<0.001), TNM stage (OR = 2.38, 95%CI 1.36–4.18, P=0.002), lymph node metastasis (OR = 2.59, 95%CI 1.25–5.36, P=0.011), degree of differentiation (OR = 2.65, 95%CI 1.54–4.58, P<0.001). However, other clinicopathologic features included age (OR = 1.07, 95%CI 0.87–1.32, P=0.516), gender (OR = 0.95, 95%CI 0.77–1.19, P=0.668), and histology (OR = 0.72, 95%CI 0.48–1.10, P=0.128) were no significant differences with high expression of MIAT. Conclusions: Our study found that overexpression of MIAT is related to poor overall survival and clinicopathological features. MIAT can be regarded as a new tumor marker to help diagnose tumors earlier, improved patient prognosis.